The Role Of Work-Related Depression And Work-Life Balance As Mediating Variables In The Relationship Between Micromanagement And Organizational Commitment: An Empirical Study On Generation Z In Solo Raya - Mauliarini, Luthfatul Anisa; Sidiq Permono Nugroho (Amkop Management Accounting Review (AMAR), 2026)
Micromanagement can strongly shape Generation Z employees’ loyalty, with work-life balance and job-related depression acting as key mediators. This study used a quantitative survey with online Likert-scale questionnaires, targeting 18–28-year-old respondents in Solo Raya who had at least one year of work experience. Secondary literature supported the theoretical base. In this research, micromanagement means excessive oversight of tasks, work-related depression reflects stress from prolonged work pressure, work-life balance is the ability to handle personal and professional roles without conflict, and organizational commitment captures employees’ attachment and loyalty to their organization. Data were analyzed using PLS-SEM via SmartPLS, testing direct and mediated relationships, with validity, reliability, path coefficients, and mediation effects assessed at p < 0.05. Results indicate that micromanagement negatively affects organizational commitment both directly and indirectly. Excessive control increases work pressure, reduces work-life balance, and harms psychological well-being, with effects particularly pronounced for Generation Z, who value flexibility, autonomy, and mental health. The findings suggest organizations should adopt supportive, trust-based leadership to enhance employee well-being and commitment.